Alpha1-antitrypsin ameliorates islet amyloid-induced glucose intolerance and β-cell dysfunction - Júlia Rodríguez-Comas; Juan Moreno-Vedia; Mercè Obach; Carlos Castaño; Sara de Pablo; Gema Alcarraz-Vizán; Daniela Díaz-Catalán; Anna Mestre; Raquel Horrillo; Montserrat Costa; Anna Novials; Joan-Marc Servitja (Elsevier, 2020)
Objective: Pancreatic β-cell failure is central to the development and progression of type 2 diabetes (T2D). The aggregation of human islet amyloid polypeptide (hIAPP) has been associated with pancreatic islet inflammation and dysfunction in T2D. Alpha1-antitrypsin (AAT) is a circulating protease inhibitor with anti-inflammatory properties. Here, we sought to investigate the potential therapeutic effect of AAT treatment in a mouse model characterized by hIAPP overexpression in pancreatic β-cells. Methods: Mice overexpressing hIAPP (hIAPP-Tg) in pancreatic β-cells were used as a model of amyloid-induced β-cell dysfunction. Glucose homeostasis was evaluated by glucose tolerance tests and insulin secretion assays. Apoptosis and amyloid formation was assessed in hIAPP-Tg mouse islets cultured at high glucose levels. Dissociated islet cells were cocultured with macrophages obtained from the peritoneal cavity. Results: Nontreated hIAPP-Tg mice were glucose intolerant and exhibited impaired insulin secretion. Interestingly, AAT treatment improved glucose tolerance and restored the insulin secretory response to glucose in hIAPP-Tg mice. Moreover, AAT administration normalized the expression of the essential β-cell genes MafA and Pdx1, which were downregulated in pancreatic islets from hIAPP-Tg mice. AAT prevented the formation of amyloid deposits and apoptosis in hIAPP-Tg islets cultured at high glucose concentrations. Since islet macrophages mediate hIAPP-induced β-cell dysfunction, we investigated the effect of AAT in cocultures of macrophages and islet cells. AAT prevented hIAPP-induced β-cell apoptosis in these cocultures without reducing the hIAPP-induced secretion of IL-1β by macrophages. Remarkably, AAT protected β-cells against the cytotoxic effects of conditioned medium from hIAPP-treated macrophages. Similarly, AAT also abrogated the cytotoxic effects of exogenous proinflammatory cytokines on pancreatic β-cells. Conclusions: These results demonstrate that treatment with AAT improves glucose homeostasis in mice overexpressing hIAPP and protects pancreatic β-cells from the cytotoxic actions of hIAPP mediated by macrophages. These results support the use of AAT-based therapies to recover pancreatic β-cell function for the treatment of T2D.